Analysis of biochemical basis of resistance mechanism of aonla (Emblica officinalis) varieties against blue mould rot disease (Penicillium islandicum) - SAINI, ANIL KUMAR; SHARMA, SUSHIL KUMAR; KUMAR, ANIL; KUMAR, PANKAJ; SINGH, DHARMENDAR (The Indian Journal of Agricultural Sciences, 2018)
Experiment was carried out at Chaudhary Charan Singh Haryana Agricultural University, Hisar to understand biochemical basis of resistance under in vitro conditions in aonla (Emblica officinalis Gaertn.). In biochemical basis of resistance, it was observed that TSS (total soluble solids), total phenol, peroxidase (PO) and polyphenol oxidase activity (PPO) was higher in diseased fruits in comparison to healthy fruits. TSS and total phenol increased in healthy and diseased fruits over time interval (5 and 10 days after inoculation). The titrable acidity was significantly lower in susceptible varieties, viz. Chakaiya (healthy fruit, 1.22 % and diseased fruit, 0.98 %) and Banarasi (healthy fruit, 1.40 % and diseased fruit, 1.32 %) as compared to resistant varieties Desi (healthy fruit, 1.50 % and diseased fruit, 1.42 %) and Kanchan (healthy fruit, 1.52 % and diseased fruit, 1.51 %). Ascorbic acid in resistant varieties Desi and Kanchan was 482.03 and 500.93 mg/100 g m aonla pulp in healthy fruits while 465.59 and 476.18 mg/100 g aonla pulp in diseased fruits after 10 days of storage. PO and PPO was found to be significantly higher in diseased fruits of resistant varieties, i.e. Desi (145, 20.49 OD/min/g) and Kanchan (139, 19.50 OD min/g) as compared to diseased fruits of susceptible Chakaiya (120, 16.19 OD/min/g) and Banarasi (118, 15.14 OD/min/g) at 5 DAI. However, the activity of PO and PPO decreased after 5 days of inoculation, while acidity and ascorbic acid was low in diseased fruits when compared to healthy fruits and further decreased over time interval. Ascorbic acid and acidity was decreased over time in both healthy and diseased fruits but at faster rate in diseased fruits as compared to healthy fruits.